Forensic psychiatric examinations of cyber criminals in Finland: court cases from the years 2015 to 2019 - Luomala, Mikko (Elsevier, 2026)
Cybercrime has become a regular phenomenon in society. This article explores cybercrime court cases from Finland between 2015 to 2019 and has any forensic psychiatric examinations made on persons who have been convicted of cybercrime. Research data was analysed with interpretative research methodology. The study has four research questions: (RQ1) How many forensic psychiatric examinations have been conducted on cybercriminals in Finland between 2015 to 2019? (RQ2) What information about the forensic psychiatric examinations has been filed in the conviction? (RQ3) How has the cybercriminal’s conviction been affected by the conducted forensic psychiatric examinations? (RQ4) Have any persons who were considered acting without sanity been sent for involuntary psychiatric treatment between 2015 to 2019? From the court documents of N=364, only 4 cases identified the mental health of the individuals was assessed, who had been convicted of cybercrime. They are all males. The forensic psychiatric examination or information relating to the mental health of the defendants in court documents lowered the sentences of the individual. There were no persons who would be declared to be criminally insane (no criminal capacity). One individual was declared by the court to be in a condition of diminished criminal capacity during the act of cybercrime. The criminal justice system and the healthcare system should prepare that forensic psychiatric examinations relating to offenders of cybercrime might increase in future because cybercrime is becoming a regular crime trend. The novelty is discussed and the study expanded understanding of the phenomena of characteristics of cybercriminals.
Keywords: cybercriminology; forensic informatics; criminal patients; forensic psychiatric examinations; conviction data; mental health; cybercrime; Finland; criminally insane; no criminal capacity; diminished criminal capacity; fi=Tietojärjestelmätiede|en=Information Systems Science|